"Nobody understands what is beautiful and what is not": Governing Soviet Amateur Photography, Photography Clubs and the Journal Sovetskoe Foto. (2nd January 2019) - Werneke, Jessica
Abstract: In January 1957, the Soviet Ministry of Culture resumed publication of the premiere photography journal of the Soviet Union, Sovetskoe foto ( The Soviet Photo ) after a 16-year hiatus. At this time, the relative openness of the Cultural Thaw fostered a "climate of enthusiasm" among amateur photographers, who were eager to learn from the professional photographers and editors of Sovetskoe foto . In the late 1950s and early 1960s, amateur and professional photographers alike sought to establish particular aesthetic standards in photography in an attempt to receive State funding and better educational opportunities. The question of who should regulate and censor amateur activities and aesthetics, however, remained ambiguous.